Mobile learning: Theoretical underpinnings - Imtinan, Umera; Chang, Vanessa; Issa, Tomayess (IADIS Press, 2012)
Mobile devices are becoming popular tools for learning among learner community in both formal and informal spaces; there is a dire need for researching and conceptualizing mobile learning to assist education providers and educational authorities to include mobile learning into mainstream education. A number of mobile learning researchers borrowed traditional learning models as theoretical foundations for mobile learning research. However, theories from a diverse range of subject areas such as Education, IS, Human-Computer Interaction and Telecommunication Engineering have also been used as the bases for mobile learning projects around the world. This incorporation of a diversity of disciplines and subjects has made mobile learning a multidisciplinary research field indeed. This paper aims to review the current theories, models, frameworks and mobile learning characteristics used by mobile learning researchers.